2015
DOI: 10.1007/s10681-015-1614-x
|View full text |Cite
|
Sign up to set email alerts
|

EMS-mutated cotton populations suggest overlapping genetic control of trichome and lint fiber variation

Abstract: The complex genetic and environmental control of lint fiber yield and quality of cotton has long motivated interest in whether information from genetically-simpler trichome variations might contribute knowledge salient to cotton improvement. To investigate this question, from 3164 M 5 lines resulting from EMS mutagenesis of two Gossypium hirsutum breeding lines, TAM 94L25 and Acala 1517-99, 106 lines with leaf and stem trichome variations and 55 control lines were further studied to investigate associations be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 70 publications
3
7
0
Order By: Relevance
“…The Gb stem trichome density was closely correlated with fuzz fiber density. These findings supplement and complement an independent study in which106 lines with leaf and stem trichome variations were shown to often have altered lint fiber characteristics, supporting the hypothesis that there is considerable overlap in the sets of genetic factors acting in the development of these analogous organs [ 33 ]. Revealing general mechanisms and specific genes regulating the density of stem trichomes will lay a foundation for understanding the mechanisms regulating the density of cotton fibers.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The Gb stem trichome density was closely correlated with fuzz fiber density. These findings supplement and complement an independent study in which106 lines with leaf and stem trichome variations were shown to often have altered lint fiber characteristics, supporting the hypothesis that there is considerable overlap in the sets of genetic factors acting in the development of these analogous organs [ 33 ]. Revealing general mechanisms and specific genes regulating the density of stem trichomes will lay a foundation for understanding the mechanisms regulating the density of cotton fibers.…”
Section: Discussionsupporting
confidence: 81%
“…Many genes were identified by homoeologous cloning and confirmed to be related to fiber development [ 2 ]. There has been long-standing interest in whether the genetics of simply inherited traits, such as trichomes in cotton, could increase our understanding of more complex processes, such as lint fiber development [ 31 , 33 ]. Simpson (1947) [ 34 ] reported that the pilose ( T 1 ) trait, which results in short dense trichomes on the vegetative parts of upland cotton, was associated with short coarse fibers.…”
Section: Discussionmentioning
confidence: 99%
“…The Gb stem trichome density was closely correlated with fuzz ber density. These ndings supplement and complement an independent study in which 106 lines with leaf and stem trichome variations were shown to often have altered lint ber characteristics, supporting the hypothesis that there is considerable overlap in the sets of genetic factors acting in the development of these analogous organs [33]. Revealing general mechanisms and speci c genes regulating the density of stem trichomes will lay a foundation for understanding the mechanisms regulating the density of cotton bers.…”
Section: Discussionsupporting
confidence: 75%
“…There has been long-standing interest in whether the genetics of simply inherited traits, such as trichomes in cotton, could increase our understanding of more complex processes, such as lint ber development [31,33]. Simpson (1947) [34] reported that the pilose (T 1 ) trait, which results in short dense trichomes on the vegetative parts of upland cotton, was associated with short coarse bers. Since then, pilose has been shown to be related to yield components and ber quality [13-14, 16, 29].…”
Section: Stem Trichomes and Seed Bers Are Epidermal Hairs That Are Rementioning
confidence: 99%